Hyaluronidase-facilitated subcutaneous immunoglobulin 10% as maintenance therapy for chronic inflammatory demyelinating polyradiculoneuropathy: The ADVANCE-CIDP 1 randomized controlled trial - Bril, Vera; Hadden, Robert D M; Brannagan, Thomas H; Bar, Michal; Chroni, Elisabeth; Rejdak, Konrad; Rivero, Alberto; Andersen, Henning; Latov, Norman; Levine, Todd; Pasnoor, Mamatha; Sacconi, Sabrina; et al. (Journal of the peripheral nervous system, 2023)
BACKGROUND AND AIMS: ADVANCE-CIDP 1 evaluated facilitated subcutaneous immunoglobulin (fSCIG; human immunoglobulin G 10% with recombinant human hyaluronidase) efficacy and safety in preventing chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) relapse. METHODS: ADVANCE-CIDP 1 was a phase 3, double-blind, placebo-controlled trial conducted at 54 sites in 21 countries. Eligible adults had definite or probable CIDP and adjusted Inflammatory Neuropathy Cause and Treatment (INCAT) disability scores of 0-7 (inclusive), and received stable intravenous immunoglobulin (IVIG) for ≥12 weeks before screening. After stopping IVIG, patients were randomized 1:1 to fSCIG 10% or placebo for 6 months or until relapse/discontinuation. fSCIG 10% was administered at the same dose (or matching placebo volume) and interval as pre-randomization IVIG. The primary outcome was patient proportion experiencing CIDP relapse (≥1-point increase in adjusted INCAT score from pre-subcutaneous treatment baseline) in the modified intention-to-treat population. Secondary outcomes included time to relapse and safety endpoints. RESULTS: Overall, 132 patients (mean age 54.4 years, 56.1% male) received fSCIG 10% (n = 62) or placebo (n = 70). CIDP relapse was reduced with fSCIG 10% versus placebo (n = 6 [9.7%; 95% confidence interval 4.5%, 19.6%] vs n = 22 [31.4%; 21.8%, 43.0%], respectively; absolute difference: -21.8% [-34.5%, -7.9%], p = .0045). Relapse probability was higher with placebo versus fSCIG 10% over time (p = .002). Adverse events (AEs) were more frequent with fSCIG 10% (79.0% of patients) than placebo (57.1%), but severe (1.6% vs 8.6%) and serious AEs (3.2% vs 7.1%) were less common. INTERPRETATION: fSCIG 10% more effectively prevented CIDP relapse than placebo, supporting its potential use as maintenance CIDP treatment.
Keywords: dospělí; safety; intravenózní imunoglobuliny; Female; Adult; výsledek terapie; ženské pohlaví; Neoplasm Recurrence, Local; chronic inflammatory demyelinating polyradiculoneuropathy; lidé; Immunoglobulins, Intravenous; chronická zánětlivá demyelinizační polyneuropatie; Treatment Outcome; hyaluronidase-facilitated subcutaneous immunoglobulin 10%; Hyaluronoglucosaminidase; Male; hyaluronoglukosaminidasa; lokální recidiva nádoru; ADVANCE-CIDP 1 randomized controlled trial; lidé středního věku; mužské pohlaví; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Middle Aged; efficacy; Humans